Combined Usage of Cryodestruction and Xenoextract to Stimulate Liver Regeneration in Rats With Experimental Cirrhosis - Olefirenko, A. A.; Tynynyka, L. N.; Sandomirsky, B. P. (Problems of Cryobiology and Cryomedicine, 2006)
The possibility to stimulate reparative processes in liver at experimental cirrhosis and a combined usage of aqueous-saline xenoextract and cryodestruction was investigated. Combined use of liver cryodestruction and xenoextract was shown as contributing to more intensive stimulation of reparative processes in cirrhotic changed liver in comparison with cryodestruction. As a result, a decrease in aminotransferase activity, bilirubin level, the normalization of peroxide processes and increase in albumin concentration in rat blood serum at the background of experimental liver cirrhosis were observed.